Reduction Of Usership In Selected Academic Institutions Ncr Delhi: A Descriptive Study - et.al, Abida Durrany (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study examines the state of university libraries in Delhi, using descriptive research and in-depth interviews with seven central universities in the city. The descriptive research included respondents such as teachers, students, and other library users. The findings identify the challenges that library users’ encounter, including the prevalence of existing libraries, traditional facilities and services, and the implementation of new policies. The one-sample t-test results for digital technologies showed P>0.05, indicating that digitization in libraries has an impact.The study's findings clearly indicated that university libraries in NCR Delhi, which are housed within existing college buildings, contain obsolete resources that are randomly arranged, giving students and teachers negative attitudes toward libraries. There are no new collections or proper electronic systems in university libraries, which has created a slew of problems for professors and students who use libraries for study. As a result, the study stresses the value of accepting technical advances that can contribute to greater levels of success